Crystal structure of an assembly intermediate of respiratory Complex II - Pankaj Sharma (Nature Portfolio, 2018)
The mechanism for covalent flavinylation of flavoenzymes is still unclear. Here, the authors propose a mechanism based on the crystal structure of a flavinylation assembly intermediate of the E. coli respiratory Complex II comprising the E. coli FrdA subunit bound to covalent FAD and crosslinked with its assembly factor SdhE.